Identifying clinical practice guidelines for the supportive care of children with cancer: A report from the Children's Oncology Group. Issue 1 (26th September 2018) - Seelisch, Jennifer; Sung, Lillian; Kelly, Michael J.; Raybin, Jennifer L.; Beauchemin, Melissa; Dvorak, Christopher C.; Kelly, Katherine Patterson; Nieder, Michael L.; Noll, Robert B.; Thackray, Jennifer; Ullrich, Nicole J.; Cabral, Sandra; et al.
Abstract: Providing evidence‐based supportive care for children with cancer has the potential to optimize treatment outcomes and improve quality of life. The Children's Oncology Group (COG) Supportive Care Guidelines Subcommittee conducted a systematic review to identify current supportive care clinical practice guidelines (CPGs) relevant to childhood cancer or pediatric hematopoietic stem cell transplant. Only 22 papers met the 2011 Institute of Medicine criteria to be considered a CPG. The results highlight the paucity of CPGs available to pediatric oncology healthcare professionals and the pressing need to create CPGs using current methodological standards.